Peran Media Sosial dalam Peningkatan Interaksi dan Citra Klub Olahraga - Nafi Aqil Fikri; Abdul Aziz Hakim; Himawan Wismanadi (Mutiara Pendidikan dan Olahraga, 2025)
Social media has a very important role, especially in the world of sports. Especially to increase interaction between sports clubs and fans in order to build a positive image of sports clubs. This research also aims to understand the role of social media to improve the interaction and image of sports clubs using an in-depth literature review. The method used is a descriptive qualitative approach and collects and provides analysis of various journal articles and sources according to the use of social media in the context of sports. The results of this study also show that social media is not only an effective communication tool, but more than that it is also a marketing tool that also increases fan loyalty, expands sponsorship, and also attracts sponsors. Effective and strategic content management also determines the success in building a positive image of the sports club. The influence of this research also states the importance of sports clubs having a professional team to effectively manage social media in order to maximize the positive impact and reduce the risks. This study also encourages further research to explore the dynamics of social media use in a sporting context.